2021
DOI: 10.1007/s00405-021-06642-7
|View full text |Cite
|
Sign up to set email alerts
|

Day case superficial parotidectomy—does it work?

Abstract: Purpose To establish if day case superficial parotidectomy is feasible, safe and does not result in excess readmissions. Method A retrospective review was carried out of all patients listed for superficial parotidectomy with day case intent by a single surgeon between January 2016 and December 2019 inclusively. The reasons for failure of same day discharge were established. Postoperative complications and readmissions were recorded. Our approach for a superficial paroti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 21 publications
(24 reference statements)
0
3
0
5
Order By: Relevance
“…In addition, the opaque dressing impeded the visual evaluation and disinfection of the wound, which may have induced an increased risk of infection (Christian et al, 2000). To following the management without any dressing (Edmond et al, 2021). Similarly, Witt showed that sialoceles could occur following PSP, and most of them would resolve without intervention within 1 month (Witt, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the opaque dressing impeded the visual evaluation and disinfection of the wound, which may have induced an increased risk of infection (Christian et al, 2000). To following the management without any dressing (Edmond et al, 2021). Similarly, Witt showed that sialoceles could occur following PSP, and most of them would resolve without intervention within 1 month (Witt, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, an elective management after PSP to prevent the aforementioned dilemmas is worth considering. In recent years, the postoperative management of PSP without any dressing has been reported (Edmond et al, 2021). Witt also found that the majority of sialoceles occurring after PSP would have been resolved without intervention within 1 month (Witt, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Insbesondere konnte kein erhöhtes Risiko einer postoperativen Nachblutung bei Operationen ohne Drainage in derzeitig vorliegenden retrospektiven Studien gezeigt werden 17 18 19 . Durch das Weglassen einer Drainage konnten jedoch die Kosten der Verbrauchsmaterialien und die Kosten durch die verringerte stationäre Liegedauer der Patienten und somit die Kosten einer Krankenhausbehandlung reduziert werden 17 18 20 . Die Aussage der oben genannten Studien muss jedoch aufgrund der retrospektiven Natur der Studien und der geringen Anzahl eingeschlossener Probanden für einen Nichtüberlegenheitsvergleich relativiert werden.…”
Section: Aktuelle Datenlage In Der Hnounclassified
“…Zum einen beziehen sich die meisten Studien, die über eine geringe Nachblutungsrate nach einer Parotidektomie von < 10 % berichten, a) vor allem auf Patientenkollektive, die nahezu ausschließlich mit einer Drainage operiert wurden, und b) auf ansonsten gesunde Patientenkollektive ohne eine Antikoagulationsstörung 2 3 . Zum anderen sind Studien, die über eine Parotidektomie mit und ohne Drainage berichten, meist retrospektiver Natur und/oder weisen eine geringe Fallzahl auf und sind schlechtweg unterpowert, sodass bis jetzt eine statistisch valide Unterlegenheit oder Gleichwertigkeit nicht gezeigt werden konnte 15 19 20 30 . Interessant ist jedoch, dass in Studien mit ambulant durchgeführten Parotidektomien teils eine Drainage eingelegt wurde, die vor Entlassung entfernt werden musste 20 .…”
Section: Zusammenfassungunclassified
See 1 more Smart Citation